Integral [ (x^2 / sqrt(4 - x^2)) dx ]
This has to be solved using trigonometric substitution.
Let x = 2sin(t). Then
dx = 2cos(t) dt, and our substitution becomes
Integral [ {4sin^2(t) / sqrt(4 - 4sin^2(t))} 2cos(t) dt ]
Skipping all the details, this reduces to
4 * Integral [ sin^2(t) ] dt
Which we use the half angle identity for
4 * Integral [ (1/2) (1 - cos(2t))] dt
2 * Integral [ 1 - cos(2t) ]
and this integrates easily now, as
2 * (t - (1/2) sin(2t)) + C, or
2t - sin(2t) + C
Using the double angle identity, we get
2t - 2sin(t)cos(t) + C
Now, since x = 2sin(t), then sin(t) = x/2 = opp/hyp
Since opp = x and hyp = 2, it follows that, by Pythagoras,
adj = sqrt(4 - x^2). This means
sin(t) = opp/hyp = x/2
cos(t) = adj/hyp = sqrt(4 - x^2)/2
Also, since sin(t) = x/2, t = arcsin(x/2). So
2t - 2sin(t)cos(t) + C
becomes
2arcsin(x/2) - 2[x/2] [sqrt(4 - x^2)/2] + C
2arcsin(x/2) - (1/2) x sqrt(4 - x^2) + C
2007-02-07 15:43:36
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
It's a trigonometric substitution.
Note that when I type o, assume I mean theta, or the Greek letter of your choice,
As it's in the form sqr(a^2-x^2), we would make x=asino, or 2sino, and we must chain rule it, therefore:
integral of: (sino)^2/sqr(4-4(sino)^2) * coso
simplify the denominator to sqr(4(1-(sino)^2)) or sqr(4(coso)^2) or 2coso. So now we have:
integral of (sin2o)^2/2 (the cosines cancel out)
pull the 1/2 out front:
1/2 * integral of (sino)^2
so
1/2 * (o/2 -sin2o/4)
or
o/4 - sin2o/8
however, now we need to go back from o's into x's, so:
x=2sino
and o = arcsin(x/2). This would make your final answer(if I'm not mistaken):
(arcsin(x/2)/4)-(x/8) + C
2007-02-07 23:58:15
·
answer #2
·
answered by yandyydna 2
·
0⤊
0⤋
Your integral has the square root of a quadratic polynomial. Whenever you have the square root of a polynomial use trigonometric substitution. In particular, factor two out of the denominator of the integrand to get
x^2/(2 sqrt(1-(x/2)^2))
make the substitution u = x /2, and then you should have one of the normal forms for trig sub.
2007-02-07 23:43:23
·
answer #3
·
answered by Sean H 5
·
0⤊
0⤋
Answer: (1/2) { -x [sq rt (4 - x^2)] + 4 [arcsin(x/2)] } + C
Integration Tables are our friends. Learn the theory, but use the tables.
2007-02-07 23:58:36
·
answer #4
·
answered by Bill C 2
·
0⤊
0⤋